Antibiotic resistance genes and bacterial communities in cornfield and pasture soils receiving swine and dairy manures. (May 2019) - Chen, Zeyou; Zhang, Wei; Yang, Luxi; Stedtfeld, Robert D.; Peng, Anping; Gu, Cheng; Boyd, Stephen A.; Li, Hui
Abstract: Land application of animal manure could change the profiles of antibiotic resistant bacteria (ARB), antibiotic resistance genes (ARGs) and bacterial communities in receiving soils. Using high-throughput real-time quantitative PCR and 16S rRNA amplicon sequencing techniques, this study investigated the ARGs and bacterial communities in field soils under various crop (corn and pasture) and manure (swine and dairy) managements, which were compared with those of two non-manured reference soils from adjacent golf course and grassland. In total 89 unique ARG subtypes were found in the soil samples and they conferred resistance via efflux pump, cellular protection and antibiotic deactivation. Compared to the ARGs in the golf course and grassland soils (28 and 34 subtypes respectively), manured soils generally had greater ARG diversity (36–55 subtypes). Cornfield soil frequently receiving raw swine manure had the greatest ARG abundance. The short-term (one week) application of composted and liquid swine manures increased the diversity and total abundance of ARGs in cornfield soils. Intriguingly the composted swine manure only marginally increased the total abundance of ARGs, but substantially increased the number of ARG subtypes in the cornfield soils. The network analysis revealed three major network modules in the co-occurrence patterns of ARG subtypes, and the hubs of these major modules ( intl1-1, vanC, and pncA ) may be candidates for selecting indicator genes for surveillance of ARGs in manured soils. The network analyses between ARGs and bacteria taxa revealed the potential host bacteria for the detected ARGs (e.g., aminoglycoside resistance gene aacC4 may be mainly carried by Acidobacteriaceae ). Overall, this study highlighted the potentially varying impact of various manure management on antibiotic resistome and microbiome in cornfield and pasture soils. Graphical abstract: Image 1 Highlights: Total 89 unique ARGs were detected in manured cornfield and pasture soils. Manured soils generally had greater ARG diversity than non-manured soils. Intl1-1, vanC, and pncA may be candidates of indicator genes for monitoring ARGs. Abstract : Manured soils generally had greater ARG diversity than non-manured soils. intl1-1, vanC, and pncA may be candidates of indicator genes for monitoring ARGs in manured soils.